2005
DOI: 10.1152/japplphysiol.00913.2004
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous adenosine and dyspnea in humans

Abstract: Intravenous adenosine for the treatment of supraventricular tachycardia is reported to cause bronchospasm and dyspnea and to increase ventilation in humans, but these effects have not been systematically studied. We therefore compared the effects of 10 mg of intravenous adenosine with placebo in 21 normal subjects under normoxic conditions and evaluated the temporal sequence of the effects of adenosine on ventilation, dyspnea, and heart rate. The study was repeated in 11 of these subjects during hyperoxia. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 53 publications
7
65
0
2
Order By: Relevance
“…Despite its dyspnoeic effect mediated by chemoreceptor activation (Burki et al 2005), adenosine is a clinically useful tool to treat supraventricular tachycardia (Biaggioni et al 1987;Riccardi et al 2008), a common cardiac rhythm disturbance more frequently observed in the elderly (Medi et al 2009). However, studies about this effect on aged subjects are yet to be made.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its dyspnoeic effect mediated by chemoreceptor activation (Burki et al 2005), adenosine is a clinically useful tool to treat supraventricular tachycardia (Biaggioni et al 1987;Riccardi et al 2008), a common cardiac rhythm disturbance more frequently observed in the elderly (Medi et al 2009). However, studies about this effect on aged subjects are yet to be made.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine cooperates with inflammatory cytokines to stimulate mucin production in the asthmatic airway (McNamara et al, 2004). Intravenous adenosine in healthy subjects does not induce bronchospasm, but causes dyspnea, most likely by an effect on vagal C fibers in the lungs (Burki et al, 2005). A more recent article claimed that all four P1 receptor subtypes play various roles in the airway responses to inhaled 5Ј-AMP in sensitized guinea pigs (Smith and Broadley, 2008).…”
Section: A Asthmamentioning
confidence: 99%
“…Conversely, drugs known to stimulate airway nociceptors have been shown to cause dyspnea in humans without affecting airway resistance. Drugs in this category include prostaglandin E 2 and adenosine (52,53).…”
Section: Dyspneamentioning
confidence: 99%